Field reports, Bob Myers, fall 1989 - Myers, Robert K.et al (1989)
Field reports by Bob Myers for fall 1989 with detailed notes for some sightings. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1989. Epson - sheet feed/flatbed